2022
DOI: 10.31629/zarah.v10i1.4253
|View full text |Cite
|
Sign up to set email alerts
|

Penerapan Model Pembelajaran Predict Observe Explain (Poe) Untuk Meningkatkan Pemahaman Konsep Dan Kemampuan Berfikir Kritis Dasar Siswa

Abstract: Model pembelajaran diperlukan agar peserta didik terlibat aktif dalam mengeksplorasi dan menerapkan konsep materi dengan baik. Salah satunya yaitu model POE (Predict-Observe-Explain). POE merupakan salah satu strategi pembelajaran yang dapat digunakan pada proses belajar  kimia seperti  memahami konsep-konsep serta penerapannya dalam kehidupan. Penelitian ini merupakan studi literatur dengan mengangkat tema terkait model pembelajaran POE. Tujuan dari penelitian ini adalah untuk mengetahui adanya dampak  penera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Based on the research results of Murtihapsari et al, (2022), looking at various aspects such as summarizing, classifying, explaining, giving examples, interpreting and concluding. All aspects studied have increased with an average value of 0.62, so it is estimated that students' POE model modules will experience an increase in understanding of concepts that have been validated by experts.…”
Section: Figure 2 Media Expert Validation Evaluatementioning
confidence: 99%
“…Based on the research results of Murtihapsari et al, (2022), looking at various aspects such as summarizing, classifying, explaining, giving examples, interpreting and concluding. All aspects studied have increased with an average value of 0.62, so it is estimated that students' POE model modules will experience an increase in understanding of concepts that have been validated by experts.…”
Section: Figure 2 Media Expert Validation Evaluatementioning
confidence: 99%
“…Penerapan model pembelajaran POE telah dilakukan pada kelas eksperimen melalui penelitian, hasil yang diperoleh menunjukkan bahwa hasil belajar peserta didik lebih baik (Andriani et al, 2017). Hal ini dikarenakan model POE melibatkan peserta didik untuk meramalkan suatu fenomena terlebih dahulu, kegiatan eksperimen atau demonstrasi dilakukan untuk observasi, kemudian hasil prediksi sebelumnya dan demonstrasi mereka dijelaskan lalu mengaitkannya dengan hasil yang didapatkan apakah sesuai dengan hasil prediksinya (Murtihapsari et al, 2022;Islamiyah et al, 2019). Artinya bahwa POE membuat peserta didik ditekankan untuk melakukan suatu kegiatan yang dapat membuktikan suatu konsep yang telah ada secara langsung, sehingga peserta didik tidak mudah melupakan konsep yang diperoleh dipikirannya (Savitri et al, 2019).…”
Section: Pembahasanunclassified
“…In this study, the researchers concluded that the POE model learning process was effective for training high school students critical thinking skills. Based on research results by Murtihapsari et al (2022), looking at various aspects such as summarizing, classifying, explaining, exemplifying, interpreting, and concluding. All aspects studied have increased with an average value of 0.62, so it can be supposed that students' POE models can experience an increase in conceptual understanding.…”
Section: Media Expert Validatormentioning
confidence: 99%